Education Budget Fluctuation and Its Relevance to the Achievement of Human Development Index on the Dimension of Education - Sanisah, Siti; Santosa, Heru (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study was aimed at revealing the relevance of the education budget to the achievement of Human Development Index on the education dimension in Central Lombok Regency of West Nusa Tenggara (NTB) Province. This study used a descriptive method with a naturalistic approach. There were 45 research subjects involved taken by applying the purposive sampling technique. Data was obtained through focused synthesis, documentation, literature study and questionnaires which were descriptively analyzed through data reduction, data display, and conclusion drawing. The results showed that the relevance index reached 0,35% (less relevant), because the financing programs and educational activities were not in line with the grand design of education. The achievement of RLS is low (6.29) and HLS (13.87) which has an impact on the minimum education index (0.59). What is indicated to have an influence is the goodwill and political will of the local government, sources of education budget, connectivity to education planning, implementation of educational programs and activities, management of education financing and commitment of education managers guided by well-managed governance.